New Ni-Anthracene Complex for Selective and Sensitive Detection of 2, 4, 6-Trinitrophenol. (6th February 2018) - Reddy, Kumbam Lingeshwar; Kumar, Anabathula Manoj; Dhir, Abhimanew; Krishnan, Venkata
Abstract : Selective and sensitive detection of explosive materials through a simple approach is an attractive area of research having implications on public safety and homeland security. Considering this implication in mind, a new Ni-anthracene complex was designed and synthesized and has been demonstrated as an efficient fluorescence chemosensor for the selective and sensitive detection of 2, 4, 6-trinitrophenol. Firstly, a fluorescent anthracene ligand (A ) was synthesized by treating anthracene-9-carboxaldehyde with 1, 3-diaminopropane in presence of a weak acid. To achieve superior selectivity and great quenching efficiency for 2, 4, 6-trinitrophenol (TNP ), a Ni complex, namely, [Ni(μ 2 -L)(NO3 )] (B ), was synthesized via the reaction ofA with Ni(NO3 )2 ·6H2 O. ComplexB showed strong emission peak (λ m a x ) at 412 nm and exhibited high selectivity towardsTNP among other nitroaromatics and anions. 100 equivalents ofTNP made 95% fluorescence quenching ofB and its detection limit forTNP was calculated as 2.8  μ M.